"Today they kill with the chair instead of the tree": Forgetting and remembering slavery at a plantation prison. (May 2017) - Kennedy, Liam
Extending the burgeoning body of work on the penal tourism industry, this project investigates how slavery is forgotten and remembered at a US plantation prison. Through a case study of Angola, I explore if and how the prison's plantation history is acknowledged at the prison rodeo and arts and crafts festival, commemorated in museum exhibits, and discussed in prisoner writings. My analysis reveals the contested nature of Angola's history and the place of slavery (and racial inequality more generally) in it. In an act of racial violence, the administration tells a story of progress that disregards slavery along with its parallels to the present. On the other hand, some prisoners resist this narrative and evoke memories of slavery in protest of their current circumstances. I conclude with a discussion of what this struggle over Angola's, and the nation's, history might mean for the prospect of penal reform.